An approach for developing diagnostic Bayesian network based on operation procedures. Issue 4 (March 2015) - Liu, Zengkai; Liu, Yonghong; Cai, Baoping; Zheng, Chao
Highlights: A method to develop Bayesian network based on operation procedures is proposed. The diagnostic model consists of faults, symptoms and operation procedures. The presented approach is applied to a case study of closing BOP. Abstract: In this paper, a novel approach of developing the Bayesian network for fault diagnosis based on operation procedures is presented. The proposed Bayesian network consists of operation procedure layer, fault layer and fault symptom layer. First, operation procedure layer containing procedure nodes and state decision nodes is developed. Second, the fault layer is determined based on the state decision nodes in the operation procedure layer. Then fault symptom layer including symptoms sensitive to the concerned faults is developed. Finally, the entire Bayesian network is established by integrating the three layers. The presented approach is applied to hydraulic control system of subsea blowout preventer (BOP). Taking an example of closing the BOP, the operation procedures are illustrated. The entire Bayesian network for fault diagnosis of closing the BOP is established. Several cases possible to appear during the closing process are studied to evaluate the developed model.